American heart association's cardiovascular health metrics and risk of cardiovascular disease mortality among a middle-aged male Scandinavian population. (18th August 2019) - Isiozor, Nzechukwu M.; Kunutsor, Setor K.; Voutilainen, Ari; Kurl, Sudhir; Kauhanen, Jussi; Laukkanen, Jari A.
Abstract: Background: The burden of cardiovascular disease (CVD) prompted the American Heart Association to develop a cardiovascular health (CVH) metric as a measure to assess the cardiovascular status of the population. We aimed to assess the association between CVH scores and the risk of CVD mortality among a middle-aged Finnish population. Methods: We employed the prospective population-based Kuopio Ischemic Heart Disease cohort study comprising of middle-aged men (42–60 years). CVH scores were computed among 2607 participants at baseline and categorized as optimum (0–4), average (5–9), or inadequate (10–14) CVH. Multivariate cox regression models were used to estimate the hazard ratios (HR) and 95% confidence intervals (CIs) of CVH score for cardiovascular mortality. Results: During a median follow-up period of 25.8 years, 609 CVD mortality cases were recorded. The risk of CVD mortality increased gradually with increasing CVH score across the range 3–14 ( p -value for non-linearity =.77). Men with optimum CVH score had HR (95% CI) for CVD mortality of 0.30 (CI 0.21 – 0.42, p < .0001) compared to those with inadequate CVH score after adjustment for conventional cardiovascular risk factors. Conclusions: CVH score was strongly and continuously associated with the risk of CVD mortality among middle-aged Finnish population and this was independent of other conventional risk factors. Key messages: Achieving optimum cardiovascular health score reduces the risk of cardiovascular mortality. Adopting the American Heart Association's cardiovascular health metrics is a welcome approach for public health awareness and monitoring of cardiovascular health among Scandinavian population.